Construction of g-C3N4/WO3/MoS2 ternary nanocomposite with enhanced charge separation and collection for efficient wastewater treatment under visible light. (May 2020) - Beyhaqi, Ahmad; Zeng, Qingyi; Chang, Sheng; Wang, Mingqi; Taghi Azimi, Seyed Mohammad; Hu, Chun
Abstract: Graphitic carbon nitride (g-C3 N4 ) has enormous potentials for photocatalysis, yet it only possesses moderate activity because of excitonic effects and sluggish charge transfer. Here, we develop a novel two-dimensional g-C3 N4 /WO3 /MoS2 (CWM) ternary nanocomposite through a facile co-calcination and a hydrothermal process to reach a highly-efficient photocatalyst for organic pollutant elimination under visible light. The WO3 and MoS2 nanoparticles were dispersed on the ultra-thin g-C3 N4 nanosheets, in which the electronegative g-C3 N4 facilitates formation of oxygen vacancies in WO3 . Compared to pure g-C3 N4, WO3, and binary composites, CWM exhibited higher photocatalytic activities for various organic pollutants removal under visible light irradiation. For instance, the CWM showed a removal ratio of ∼99% for RhB after only 10 min irradiation of visible light (λ > 420 nm) and nearly 100% for ciprofloxacin after 2 h of operation. The results showed that OH radicals are the main active species for organic degradation, which suggests a direct Z-scheme heterojunction in CWM that improved spatial separation of charge carries. Furthermore, the collection of electrons is significantly enhanced by MoS2 for oxygen reduction reaction, and the increased oxygen vacancies of WO3 further enhanced the separation of electron-hole pairs; therefore, it led to an effective suppression of charge carriers recombination. The above synergistic effects of ternary photocatalyst result in higher photocatalytic oxidation performance for wastewater treatment compared with pure WO3, g-C3 N4 and their binary composites. Graphical abstract: Efficiently improved organics and dyes degradation system is acquired using a 2-D g-C3 N4 /WO3 /MoS2 ternary nanocomposite which has improved spatial separation of charge carries and facilitated collection of electrons under visible light. Image 1 Highlights: 2-D CWM was constructed through a facile co-calcination and a hydrothermal process. Electronegative g-C3 N4 facilitates the formation of oxygen vacancies in WO3 . High rates of degradation are obtained for various organic contaminants under visible light. The CWM shows Z-scheme heterostructure in photogenerated charges separation. MoS2 further hinders the charge recombination by consuming electrons for ORR.